Protective Effects of Diallyl Sulfide against Thioacetamide-Induced Toxicity: A Possible Role of Cytochrome P450 2E1 - Kim, Nam Hee; Lee, Sangkyu; Kang, Mi Jeong; Jeong, Hye Gwang; Kang, Wonku; Jeong, Tae Cheon (Biomolecules & therapeutics, 2014)
Effects of diallyl sulfide (DAS) on thioacetamide-induced hepatotoxicity and immunotoxicity were investigated. When male Sprague-Dawley rats were treated orally with 100, 200 and 400 mg/kg of DAS in corn oil for three consecutive days, the activity of cytochrome P450 (CYP) 2E1-selective p-nitrophenol hydroxylase was dose-dependently suppressed. In addition, the activities of CYP 2B-selective benzyloxyresorufin O-debenzylase and pentoxyresorufin O-depentylase were significantly induced by the treatment with DAS. Western immunoblotting analyses also indicated the suppression of CYP 2E1 protein and/or the induction of CYP 2B protein by DAS. To investigate a possible role of metabolic activation by CYP enzymes in thioacetamide-induced hepatotoxicity, rats were pre-treated with 400 mg/kg of DAS for 3 days, followed by a single intraperitoneal treatment with 100 and 200 mg/kg of thioacetamide in saline for 24 hr. The activities of serum alanine aminotransferase and aspartate aminotransferase significantly elevated by thioacetamide were protected in DAS-pretreated animals. Likewise, the suppressed antibody response to sheep erythrocytes by thioacetamide was protected by DAS pretreatment in female BALB/c mice. Taken together, our present results indicated that thioacetamide might be activated to its toxic metabolite(s) by CYP 2E1, not by CYP 2B, in rats and mice.